Let o = 61 - 57. Solve g = 2*g + o for g.

-4

Let c(p) = p**2 + 8*p + 16. Let z be c(-6). Solve g = -0 + z for g.

4

Suppose 0 = -6*i + 3*i + 3. Let k(v) = 6*v. Let u be k(i). Let j = u + -6. Solve c = -j*c for c.

0

Let p(b) = -b3 + b2 + b + 2. Let a be p(0). Solve -a = q + 1 for q.

-3

Let p be (-23)/(-3) + 13. Let g® = -r2 - r + 2. Let t(j) = -5*j2 - 5*j + 11. Let b© = 11*g© - 2*t©. Let y be b(-1). Solve 3*f - 7 - p = y for f.

5

Suppose -7 - 7 = -r. Suppose -r - 61 = -5*w. Solve t - 4*t = -w for t.

5

Let p be 3610 + (-24)/40. Suppose -p*s + 2 = -13. Let g be 2/(312*2). Solve 0 = s*b - g - 6 for b.

2

Let r(t) = -2*t + 1. Let k be r(3). Let h = k + 9. Suppose s = -3*s + 4, 3*l = h*s + 2. Solve -l*y = -2 + 10 for y.

-4

Suppose -3*w + 3*s = -0*s - 9, 3*w + 4*s + 12 = 0. Let c = -16 + 18. Solve 0*q - q - c = w for q.

-2

Suppose 0*n = -n - 4*k - 2, 3*k = 5*n - 13. Solve -n - 2 = 4*y for y.

-1